(untitled) (Fiep Bulletin - online, 2015)
One of the most present problems for athletes, trainers or sport physicians is the evaluation of the load imposed to the musculature. Usually the people only notice that they were exceeded in muscular works when they feel pains and have an installed lesion. Evaluate in a refined way the muscular overload is, therefore, a longing of all those that work with physical activities. This study aimed to establish an index capable to serve as a reference tool of the wear and tear state imposed to the musculature. For this, 1037 diagnoses accomplished according to the Biochemical-hematological Monitoration of the Physical Conditioning (BHMPC®) method (Cosendey, 1997) were selected. The sample was composed by 990 adults (460 athletes and 530 no-athletes), appraised in a period of five years in the Laboratory of Biochemistry of the Sport, in Rio de Janeiro. The relationships among 75 indicative variables of the physiologic behavior of the organism and intervening in organic biochemical processes linked to the of level of muscular stress, were quantified and transformed in an adimentional numeric index, that allows to represent the stress degree imposed to a person’s musculature. Like this, it was established the Index of Muscular Stress (IME), that can vary in a range of 18358 levels, from the minimum (44) until the maximum (18402). The calculated ideal strips, corresponding to appropriate muscular requests, was those located among the values from 150 to 210 for male athletes and from 138 to 193 for female athletes. For no athletes, the calculated ideal strip was located between 110 and 170 for men and between 101 and 156 for women. It was concluded that the adoption of IME allows to detect and to accompany better the physical condition of anybody, supplying a reliable quantitative data for the health and individual performance quality preservation.